Histopathological Findings in Cholecystectomy Specimens of Gallbladder in a Tertiary Care Hospital in Kathmandu: A Descriptive Cross-Sectional Study - Maharjan, Rajendra; Khadka, Rajya (Medical Journal of Armed Police Force Nepal, 2025)
Introduction: Gallbladder specimen is frequently examined in a surgical pathology practice. It presents with a wide spectrum of lesions on histopathology. The gallbladder is among the most common organs where incidental carcinoma can occur. The study aimed to determine the various histopathological spectrum of gallbladder specimens and their prevalence in a tertiary care hospital in Kathmandu. Methods: This cross-sectional study was conducted in the Pathology department of a tertiary care hospital between January 1, 2023, and December 30, 2024. Ethical approval (Reference number: NAPFH-037/2024) was granted by the Institutional Review Committee. All patients who had undergone cholecystectomy were included in the study. An enumerative sampling technique was used. Data were analyzed with Microsoft Excel and Statistical Package for the Social Sciences version 17. Results: Out of 400 cholecystectomy specimens, the most common histopathological finding was chronic cholecystitis, with specific findings in 270 (67.50%) cases. 11 (2.75%) cases of dysplasia and one (0.25%) case of gallbladder adenocarcinoma were found. There were 125 (31.25%) males and 275 (68.75%) females. Male to female ratio was 1:2.2. The age ranged from 15 to 83 years, and the mean age was 44.32±13.55 years. Maximum number of lesions of gallbladder was observed in the 30-39 years age group, with 136 (34%) cases. Conclusions: The prevalence of chronic cholecystitis with specific finding is high among histopathological findings of gallbladder specimens. Gallbladder diseases are more common in third to fourth decades with female preponderance. Incidental gallbladder carcinoma though rare may present in the routine histopathology of gallbladder specimens.